Pengembangan Jurusan Zakat Dan Wakaf Pada UIN SMH Banten - Masykuroh, Nihayatul; Peristiwo, Hadi; Suganda, Asep Dadan (STIE Malangkucecwara, 2019)
This feasibility study aims to determine the extent of the community interest towards opening the Department of Zakat and Endowments Management at the Faculty of Islamic Economics and Business, UIN SMH Banten. The method of this research used descriptive qualitative by distributing questionnaires to the students of High School (SMA), Vocational School (SMK) and Islamic High School (MA) in Serang City. Furthermore, guided interviews were conducted for philanthropic institutions such as BAZNAS, Indonesian Endowments Agency (BWI), Dompet Dhu’afa, and LAZ Harfa. In addition, most respondents were very interested in continuing their studies to a higher level, both the respondents from the public school and private schools as many as 83.1%. Whereas the respondents' interest in continuing their studies in FEBI, UIN SMH Banten, when the Department of Zakat and Endowments Management has been opened, is 49.2%, with the most preferred area of ​​respondents when entering the Department of Zakat and Endowments Management was the management area, which is equal to 76.3%. Based on these data, it can be stated that the Department of Zakat and Endowments Management is feasible to be opened in FEBI, UIN SMH Banten.